(untitled) (Research, Society and Development, 2025)
Objective: To document the planning and methodological processes of a scoping review protocol aimed at mapping the current scientific knowledge on TEMPI Syndrome. Introduction: TEMPI Syndrome is a rare, acquired, and multisystemic disease characterized by telangiectasias, elevated erythropoietin levels and erythrocytosis, monoclonal gammopathy, perinephric fluid collections, and intrapulmonary shunting. Justification: Due to its rarity, we hypothesize that the lack of awareness regarding this syndrome may lead to misdiagnosis or delayed diagnosis. A systematic literature review can contribute to increasing knowledge and dissemination of information on the topic. Methodology: The protocol was registered in the Open Science Framework and structured following the five-stage methodological framework by Arksey & O’Malley (2005), in accordance with the Joanna Briggs Institute guidelines. The review is guided by the question: "How can the available scientific evidence contribute to improving the diagnosis and comprehensive care of patients with TEMPI Syndrome?" A systematic search will be conducted in the Medical Literature Analysis and Retrieval System (MEDLINE) and in the Biblioteca Virtual em Saúde (BVS), without time restrictions. Gray literature will be retrieved using Google Scholar. Two independent reviewers will screen studies for eligibility. Results: Findings will be reported in accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) and presented in tabular and narrative formats aligned with the study objectives and research question.